2014
DOI: 10.1097/qco.0000000000000080
|View full text |Cite
|
Sign up to set email alerts
|

Back to basics

Abstract: Purpose of reviewHand hygiene and isolation are basic, but very effective, means of preventing the spread of pathogens in healthcare. Although the principle may be straightforward, this review highlights some of the controversies regarding the implementation and efficacy of these interventions.Recent findingsHand hygiene compliance is an accepted measure of quality and safety in many countries. The evidence for the efficacy of hand hygiene in directly reducing rates of hospital-acquired infections has strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 92 publications
0
14
0
2
Order By: Relevance
“…Staff should receive education on the importance of PHH in the prevention of hospital-acquired infection; and staff need to be instructed to provide verbal PHH education to all newly admitted patients, and to provide reminders, assistance and encouragement for PHH practice 16 17. In addition, it is also important to ensure that HH products—such as alcohol-based hand wipes or ABHR—are accessible to patients who are bedridden and are unable to get to the sink 18 19. Staff or family members should be instructed to provide assistance to improve PHH opportunities 18…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staff should receive education on the importance of PHH in the prevention of hospital-acquired infection; and staff need to be instructed to provide verbal PHH education to all newly admitted patients, and to provide reminders, assistance and encouragement for PHH practice 16 17. In addition, it is also important to ensure that HH products—such as alcohol-based hand wipes or ABHR—are accessible to patients who are bedridden and are unable to get to the sink 18 19. Staff or family members should be instructed to provide assistance to improve PHH opportunities 18…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is also important to ensure that HH products—such as alcohol-based hand wipes or ABHR—are accessible to patients who are bedridden and are unable to get to the sink 18 19. Staff or family members should be instructed to provide assistance to improve PHH opportunities 18…”
Section: Discussionmentioning
confidence: 99%
“…In order to minimize the risk of acquiring an opportunistic infection, patients benefit from strict compliance with infection prevention and control 38 . More efforts should be invested in creating better awareness for this issue amongst medical personal.…”
Section: Discussionmentioning
confidence: 99%
“…organ transplantation post-op, could have beneficial effects. Although a recent review showed that noncompliance resulted in a paradoxical increase in adverse events 38 .…”
Section: Discussionmentioning
confidence: 99%
“…The long-term survival of these bacteria in the environment increases their chance of transmission to sensitive hosts via the ingestion of such contaminated products, food and water, or through their contact with such inanimate objects [ 6 , 10 , 17 , 37 ]. Furthermore, farm personnel also play a role in transmission of bacteria within and among the farms through their contact with contaminated hands, clothes and boots [ 4 , 16 , 18 , 36 ].…”
mentioning
confidence: 99%